«Хто серед безтілесних божеств найбільш озброєний?» (втілення Веретрагни за 14-м Яштом) - Вертієнко, Г.В. (Археологія і давня історія України, 2015)
Надається вибірковий переклад 14 Яшта Молодшої Авести на українську мову з описом десяти втілень-іпостасей іранського військового божества Веретрагни (Яшт 14, 2, 7, 9, 11, 15, 17, 19, 23, 25, 27). В статье дан перевод с авестийского языка на
украинский фрагментов 14 Яшта (Бахрам-Яшта)
с описанием десяти ипостасей иранского воинского
божества победы Веретрагны (Яшт 14, 2, 7, 9, 11, 15,
17, 19, 23, 25, 27): ветра-Ваты (схварно, исцелением и мощью), быка, коня, верблюда, кабана, пятнадцатилетнего, птицы-варегна, барана, козла, воина (с кинжалом). В скифологии существуют гипотезы
относительно возможности отображения на различных произведениях скифоакского звериного стиля
зооморфных образов Веретрагны, известных по описанию в 14 Яште. In this paper the translation from Avestan language
to Ukrainian of the 14 Yasht (Bahram-Yasht) parts
with the description of ten forms of the Iranian military
deity of victory Verethragna (Yasht 14, 2, 7, 9,
11, 15, 17, 19, 23, 25, 27) is provided: Vata-wind (with
hvarno, healing and power), a bull, a horse, a camel,
a boar, a fifteen-year-old man, a varegna-bird, a ram,
a goat, a warrior (with dagger). There are hypotheses
in Scythology concerning possibility of display on different
Skythian-Sakas animal style products of the
zoomorphic images of Verethragna are known from the
text of Yasht 14.